Gender and Racial Inequality at Work: The Sources and Consequences of Job Segregation - Andiappan, P. (Relations industrielles / Industrial Relations, 1996)
The article reviews the book, "Gender and Racial Inequality at Work: The Sources and Consequences of Job Segregation," by Donald Tomaskovic-Devey.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Equality; Human capital; Human resource management; Labor Unions; Management science; Race; Segregation; Sexes; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z